Neuro-behavioral manifestations of Prader-Willi syndrome : a guide for clinicians and caregivers - Singh, Deepan (Cambridge : Cambridge University Press, 2022)
The behavioral issues experienced by individuals with Prader-Willi Syndrome (PWS) can be both surprising and overwhelming to clinicians and caregivers. Despite the distress and dysfunction posed by them, there are very few resources available to address these neuropsychiatric problems. This invaluable guidebook helps to identify and address the spectrum of behavioral issues faced by individuals with PWS. Written by a psychiatrist with unique expertise in the management of patients with this condition, this easy-to-read book explores practical details that will aid any clinician or caregiver. Chapters offer vivid case examples and clear guidance on both the behavioral and pharmacological management of issues such as anxiety, skin-picking, ADHD, disruptive behavior (including non-suicidal self-harm), mood disorders (including depression and bipolar disorder), and psychosis. Neuro-behavioral Manifestations of Prader-Willi Syndrome serves as an essential and practical companion for any caregiver or healthcare professional providing care to people with PWS.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Prader-Willi syndrome